Substitution Relationship Between The Agency Problem Control Mechanisms in Malaysia: Simultaneous Equation Analysis - D. Agus Harjito (Jurnal Siasat Bisnis, 2006)
This study investigates the substitution relationship (substitutability) between debt policy, insider ownership, and dividend policy as the agency problem control mechanism in Malaysia. If the substitution relationship exists between the agency control mechanisms, the agency problem can be reduced through this relationship. Reducing the agency problem as a result can increase the firm value proxied by Tobin’s Q. This study employs 396 firms sample listed on Malaysian Bourse from 2001 to 2004. To achieves the objectives, this study uses two-stage least square method. The results of this study indicate that the substitutability between debt policy, insider ownership, and dividend policy as agency problem control mechanism does not fully exist in Malaysia. Apparently the substitutability only exists for debt policy and dividend. There is no substitution between debt policy and insider ownership as well as between dividend policy and insider ownership. Key words: debt policy, insider ownership, dividend policy, agency problem, firm value